The handbook for investment committee members : - Olson, Russell L. (Wiley, 2005)
In a clear, organized, and easy-to-understand manner, this handbook explains the responsibilities and expectations of investment committee fiduciaries for pension funds, endowment funds, and foundations. Emphasizing all the do's and don'ts to follow for prudent investment management, this invaluable resource covers topics ranging from investment policy, asset allocation, and risk assessment to understanding information presented at committee meetings, asking meaningful and productive questions, and voting on recommendations knowledgeably. This book will empower readers with all the knowledge they need to feel confident in the investment decisions they make for their organizations